2000
DOI: 10.4315/0362-028x-63.4.427
|View full text |Cite
|
Sign up to set email alerts
|

A Microscopic Method to Visualize Escherichia coli Interaction with Beef Muscle

Abstract: The genetic determinant for enhanced green fluorescent protein (EGFP) was introduced into Escherichia coli JM109 (ATCC 53323) and E. coli O157:H7 (ATCC 43895) on plasmid EGFP. The expression of EGFP did not change the growth kinetics or surface properties tested (hydrophobicity and electrophoretic mobility). Microscope slides were modified to allow for optimal viewing of thick meat samples with an inverted microscope. Two fluorescent dyes, nile red and Cy3 were used to stain for lipid and protein portions of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…It has been shown before that bacterial strains with similar hydrophobic properties show similar adhesion patterns to surfaces and that hydrophobic surfaces favor adhesion of hydrophobic bacteria (21). The relative hydrophobicity of the bacterial strains used in this work was measured using their adhesion to both hexadecane and xylene, since the results of hydrocarbon attachment measurements may vary depending on the hydrocarbons tested (20). In this study, the attachment results were similar for hexadecane and xylene, as shown by the data in Table 1.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…It has been shown before that bacterial strains with similar hydrophobic properties show similar adhesion patterns to surfaces and that hydrophobic surfaces favor adhesion of hydrophobic bacteria (21). The relative hydrophobicity of the bacterial strains used in this work was measured using their adhesion to both hexadecane and xylene, since the results of hydrocarbon attachment measurements may vary depending on the hydrocarbons tested (20). In this study, the attachment results were similar for hexadecane and xylene, as shown by the data in Table 1.…”
Section: Resultssupporting
confidence: 62%
“…These values represent the percentage of cells that did not adhere to the hydrocarbons and remained in the aqueous phase. Cells are considered relatively hydrophobic when the values of the OD 540 ratios are closer to 0 (indicating fewer cells remaining in aqueous phase) and relatively hydrophilic when the values are closer to 1 (20). Experiments were conducted in triplicate, and the values reported are average values with the standard deviation of three measurements.…”
Section: Methodsmentioning
confidence: 99%
“…GFP-expressing bacteria have been previously used in a number of studies that did not involve intact, living animals (21)(22)(23)(24)(25)(26)(27)(28)(29)). An example of such studies was the visualization of the in vitro infection of muscle tissue by the pathogenic E. coli O157H GFP (28).…”
Section: Discussionmentioning
confidence: 99%
“…An example of such studies was the visualization of the in vitro infection of muscle tissue by the pathogenic E. coli O157H GFP (28). Another approach examined the mouse gastrointestinal tract after gavage infection by removal and fixation of the gastrointestinal tissue (29).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella/pEGFP strains were only grown on media supplemented with antibiotic. Prachaiyo and McLandsborough (27) found that when grown without antibiotic selection, approximately 90% of the cell population lost the plasmid over the course of an 8-h culture. Transformed Salmonella strains inoculated onto LBA-amp plates, incubated for 12 to 16 h, and stored at 4ЊC stably maintained the pEGFP plasmid for over 30 days.…”
Section: Stability Of Egfp Expression By Salmonella Strainsmentioning
confidence: 99%